STATUS HUKUM DAN HAM ANAK DALAM SISTEM PERADILAN PIDANA ANAK DI INDONESIA - Habib Shulton Asnawi (Istinbath : Jurnal Hukum, 2015)
Background This article departs from concern about the high violation of children's rights in Indonesia, particularly children in conflict with the law (child in conflict with the law), either as witnesses, victims or perpetrators of crime. In this article, focusing on the study of the question of the juvenile criminal justice system, namely Law. No. 11 of 2012 on the Criminal Justice System Child (Law SPPA), which still left many problems so that justice and the rights of children difficult to materialize. However, it should be realized that the product legislation is the result of a political compromise so much criticism even guguatan shown in SPPA law shortly after enactment. Although, on the other hand the Act SPPA lot of progress compared to the previous juvenile justice law. Therefore, in this article that will be studied is what are the issues in the Act SPPA and how efforts to optimize the Act SPPA in justice and human rights protection for children in Indonesia against the law.